2014
DOI: 10.1021/jm500038p
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesive Properties of Glycoclusters against Pseudomonas aeruginosa Lung Infection

Abstract: Pseudomonas aeruginosa lung infections are a major cause of death in cystic fibrosis and hospitalized patients. Treating these infections is becoming difficult due to the emergence of conventional antimicrobial multiresistance. While monosaccharides have proved beneficial against such bacterial lung infection, the design of several multivalent glycosylated macromolecules has been shown to be also beneficial on biofilm dispersion. In this study, calix[4]arene-based glycoclusters functionalized with galactosides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 51 publications
3
127
0
Order By: Relevance
“…[78] To treat these infections is becoming difficult day by day due to emergence of antimicrobial multiresistance against most of the available drugs. Recently, keeping in view the beneficial effect of monosaccharides against such bacterial lung infections, [79] Vidal and co-worker [80] have synthesized several multivalent calix [4]arene-based glycoclusters of type 12 (Scheme 7) through azide-alkyne 1,3-dipolar cycloaddition and characterized their antiadhesive properties against Pseudomonas aeruginosa through several in vitro bioassays. Interestingly, the designed glycoclusters have provided an almost complete protection against Pseudomonas aeruginosa in mouse model (in vivo) of lung infection.…”
Section: S C H E M E 2 Synthesis Of Calixcephem 5 S C H E M E 3 Synthmentioning
confidence: 99%
“…[78] To treat these infections is becoming difficult day by day due to emergence of antimicrobial multiresistance against most of the available drugs. Recently, keeping in view the beneficial effect of monosaccharides against such bacterial lung infections, [79] Vidal and co-worker [80] have synthesized several multivalent calix [4]arene-based glycoclusters of type 12 (Scheme 7) through azide-alkyne 1,3-dipolar cycloaddition and characterized their antiadhesive properties against Pseudomonas aeruginosa through several in vitro bioassays. Interestingly, the designed glycoclusters have provided an almost complete protection against Pseudomonas aeruginosa in mouse model (in vivo) of lung infection.…”
Section: S C H E M E 2 Synthesis Of Calixcephem 5 S C H E M E 3 Synthmentioning
confidence: 99%
“…Almost ten years have passed since the seminal review [2] notably for the control of P. aeruginosa adhesion and biofilm formation [78,79]. Although FimHmediated adhesion seems to be effectively controlled also by monomannosides of extended aromatic aglycones, most of the current antiadhesive technologies employ high-valency glycoclusters.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In addition, these monosaccharides displayed synergistic effect when used in combination with antibiotics such as b-lactams and fluoroquinolone [88]. In a recent study, multivalent glycosylated macromolecules functionalized with galactosides or fucoside for lectin targeting were designed to combat P. aeruginosa infection [89]. The authors demonstrated that these multivalent glycocluster inhibited bacterial adhesion while simultaneously protected host against lung injury in mouse pulmonary lung infection model [89].…”
Section: Secretion Of Conditioning Layers Irreversible Attachment Andmentioning
confidence: 99%